Hiệu quả hoạt động của các trường trung học phổ thông chuyên vùng đồng bằng sông Cửu Long theo yêu cầu đổi mới giáo dục - Lê, Văn Nhương; Trần, Thanh Bình; Huỳnh, Anh Huy (Tạp chí Giáo dục, 2025)
In the context of comprehensive educational innovation and the need to develop high-quality human resources to serve the socio-economic development of the Mekong Delta, the system of specialized high schools plays an important role in discovering and nurturing excellent students and young talents. This article evaluates the effectiveness of the system of specialized high schools in the Mekong Delta through a survey of 166 managers and teachers from 15 specialized high schools and some nonspecialized schools. The survey results show the strengths and weaknesses of the current system and the consensus on innovative solutions in management, teaching content and teaching methods, aiming to improve the quality and adaptability of specialized high schools. The study has provided a scientific basis for policies to develop the system of specialized high schools in the Mekong Delta, contributing to improving the quality of human resource training for the region.